The effects of ethnomathematics education on student outcomes: The JADENKÄ program in the Ngäbe-Buglé Comarca, Panama - Emma Näslund-Hadley; Juan Manuel Hernández-Agramonte; Carmen Albertos; Ana Grigera; Cynthia Hobbs; Horacio Alvarez (Inter-American Development Bank (IDB), 2022)
In this article we evaluate the effectiveness of ethnomathematics education among indigenous children: the JADENKÄ program. This intercultural bilingual program has been designed to strengthen the mathematical and ethnomathematical skills of the Ngäbe preschoolers in Ngäbe-Buglé, a comarca in Panama. The results of our experiment suggest that the program has improved the students' mathematical and ethnomathematical skills. The magnitude of the impact on mathematics, of 0.12-0.18 standard deviations (s.d.), is comparable to preschool programs that teach intercultural bilingual classes in low- and middle-income countries. In ethnomathematics, the impact is around 0.23 s.d. Additionally, and consistent with other studies, we find that JADENKÄ has a beneficial effect on the cultural identity of students. Second, results suggest that the effect of the program in ethnomathematics is stronger among Ngäbere-speaking students and for students whose teachers identify as Ngäbe. Finally, the program bolstered teachers' ethnomathematical skills and also their knowledge of the Ngäbere language and culture. Contrary to the views of some critics, we find that a well-designed ethnomathematics program can reduce the indigenous achievement gap without asking students to choose between their academic learning and their identity, culture, and language.
Keywords: C21; I24; J15; 330; Ethnomathematics; Intercultural Bilingual Education; Randomized Controlled Trial